Metode MimMem dalam Pembelajaran Bahasa Arab - Aufia Aisa; Vera Fikrotin (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
ABSTRACT The learning method is an important factor in the success of learning Arabic. For teaching success related to the method used. Mim stands for mimicry which means to imitate and mem is memorization which means to memorize. The Mim-mem method is useful for training students to develop their communication skills. the main purpose of this method is to use the target language communicatively. And each method has advantages and disadvantages. One of the advantages of this method is that the class will be more active, while one of the disadvantages of this method is when the learners are only able to speak without knowing the writing. Keywords: Mimicry-memorization method, Arabic Learning.